STUDY AND INTERPERTATION PIPING FAILURE OF EARTHEN LEEVE AND DAM (International Journal of Food and Nutritional Sciences, 2022)
Abstract—Piping failure is a critical phenomenon specially in earthen dam. Lot of studies conducted on piping failure on non-cohesive sandy soils. Geological trials have been conducted on s a m pl e of soil to study piping failure in an indirect manner. Experimental investigations to understand the piping erosion process are conducted and results are discussed in this paper.